Aircraft drive inverter design at physical limits - Meindl, Markus; Zettelmeier, Julius; Bentheimer, Christian; Hilpert, Florian; März, Martin (Technical Session - Power Electronics for Aircraft Electrification, 2023)
Power electronics is a hotly debated and acutely researched topic for transitioning to sustainable aviation. Power electronic systems convince with high power densities and ensure the most efficient operation of the individual components in a hybrid-electric aircraft. This paper presents the first detailed considerations for exploring the drive inverter performance limits over different time horizons (2030 and 2050) in a hybrid-electric 50-PAX regional aircraft with a possible range of 1500 km. Based on many years of experience designing highly integrated drive inverters, the physical limits concerning power-to-weight ratio and efficiency were explored based on detailed analytical considerations, taking current component technologies and their extrapolated development potentials as a basi
Keywords: Power Electronics; hybrid-electric aircraft; drive inverter; design limits

Decarbonised Future Regional Airport Infrastructure - Meindl, Markus; de Ruiter, Cor; Marciello, Valerio; Di Stasio, Mario; Hilpert, Florian; Ruocco, Manuela; Nicolosi, Fabrizio; Thonemann, Nils; Saavedra-Rubio, Karen; Locqueville Louis, Louis; Laurent, Alexis; März, Martin (Aerospace, 2023)
Sustainability and, especially, emission reductions are significant challenges for airports currently being addressed. The Clean Sky 2 project GENESIS addresses the environmental sustainability of hybrid-electric 50-passenger aircraft systems in a life cycle perspective to support the development of a technology roadmap for the transition to sustainable and competitive electric aircraft systems. This article originates from the GENESIS research and describes various options for ground power supply at a regional airport. Potential solutions for airport infrastructure with a short (2030), medium (2040) and long (2050) time horizon are proposed. This analysis includes estimating the future energy demand per day, month and year. In addition, the current flight plan based on conventional aircraft is adapted to the needs of a 50-PAX regional aircraft. Thus, this article provides an overview of the energy demand of a regional airport, divided into individual time horizon
CRIS-Team Scopus Importer:2023-04-14
Keywords: on-ground energy supply; hybrid-electric aircraft; airport infrastructure; sustainable aviation

Design Exploration for Sustainable Regional Hybrid-Electric Aircraft: A Study Based on Technology Forecasts - Marciello, Valerio; Di Stasio, Mario; Ruocco, Manuela; Trifari, Vittorio; Nicolosi, Fabrizio; Meindl, Markus; Lemoine, Bruno Eric Marc; Caliandro, Priscilla (Aerospace, 2023)
The environmental impact of aviation in terms of noise and pollutant emissions has gained public attention in the last few years. In addition, the foreseen financial benefits of an increased energy efficiency have motivated the transport industry to invest in propulsion alternatives. This work is collocated within the Clean Sky 2 project GENESIS, focused on the environmental sustainability of 50-passenger hybrid-electric aircraft from a life-cycle-based perspective to support the development of a technology roadmap for transitioning towards sustainable and competitive electric aircraft systems. While several studies have already focused on the definition of possible aircraft designs combining several propulsion systems, the novelty of the present work is to consider technology forecasts and more comprehensive indicators in the design phase. These include the performance and emissions on a 200 nmi typical mission, which reflects the most economically attractive range for aircraft in the regional class. The work proposes a complete exploration of three major technology streams for energy storage: batteries, fuel cells, and turbine internal combustion engine generators, also including possible combinations of those technologies. The exploration was carried out through the execution of several designs of experiments aiming at the identification of the most promising solutions in terms of aircraft configuration for three different time horizons: short-term, 2025–2035; medium-term, 2035–2045; and long-term, 2045–2050+. As a result, in the short-term scenario, fuel energy consumption is estimated to be reduced by around 24% with respect to conventional aircraft with the same entry-into-service year thanks to the use of hybrid propulsive systems with lithium batteries. Fuel saving increases to 45% in the medium-term horizon due to the improvement in the energy density of storage systems. By the year 2050, when hydrogen fuel cells are estimated to be mature enough to completely replace kerosene-based engines, the forthcoming hybrid-electric aircraft promise no NOx and CO2 direct emissions, while being approximately 50% heavier than conventional ones.
CRIS-Team Scopus Importer:2023-03-10
Keywords: aircraft design; distributed electric propulsion; fuel cell systems; hybrid-electric propulsion system; sustainable aviation

Design proposal and optimization potential for an electric drive motor in a 50 PAX hybrid-electric regional aircraft application - Meindl, Markus; Liu, Xinjun; Hilpert, Florian; Marciello, Valerio; Di Stasio, Mario; März, Martin (11th International Conference on Power Electronics - ECCE Asia, 2023)
Electric propulsion systems are considered one possibility to reach the ambitious goals of the European Union's Flightpath 2050 concerning greenhouse gas emissions and noise. This paper proposes an engineering architecture design of an electric motor for a propulsion system in a hybrid-electric regional aircraft. The project partners defined the performance requirements for the thrust of the propulsion system. The electric drive motor for the propellers was calculated and then simulated. This paper specifies the motor, with the materials possible for construction.<br
Keywords: electric motors; hybrid-electric aircraft; future propulsion systems; electrification

Greening Regional Airports: A Vision for Carbon Neutral Infrastructure - Meindl, Markus; de Ruiter, Cor; Marciello, Valerio; Di Stasio, Mario; Saavedra-Rubio, Karen; Laurent, Alexis; Ruocco, Manuela; März, Martin (Contemporary Perspective on Science, Technology and Research Vol. 3, 2024)
This study provides an overview of the energy demand of a regional airport, divided into individual time horizons. The electrification of aircraft systems raises the question of whether airports will be among the largest electricity consumers in our infrastructure in the future. Sustainability and especially emission reductions are significant challenges for airports that are currently being addressed. The Clean Sky 2 project GENESIS addresses the environmental sustainability of hybrid-electric 50-passenger aircraft systems in a life cycle perspective to support the development of a technology roadmap for the transition to sustainable and competitive electric aircraft systems. This article originates from the GENESIS research and describes various options for ground power supply at a regional airport. Potential solutions for airport infrastructure with a short (2030), medium (2040), and long (2050) time horizon are proposed. In addition to the environmental and conservation benefits, switching from fossil fuels to sustainably produced fuels is also financially attractive for airports, airlines, and travelers. This analysis includes estimating the future energy demand per day, month, and year. In addition, the current flight plan based on conventional aircraft is adapted to the needs of a 50-PAX regional aircraft. The findings confirm that airports will require an enormous amount of electrical energy due to the electrification of air traffic.<br
Keywords: On-ground energy supply hybrid-electric aircraft airport infrastructure sustainable aviation

Ground-Based Power Supply System to Operate Hybrid-Electric Aircraft for Future Regional Airports - Meindl, Markus; Weber, Kai Johannes; März, Martin (2023 IEEE International Conference on Electrical Systems for Aircraft, Railway, Ship Propulsion and Road Vehicles & International Transportation Electrification Conference (ESARS-ITEC), 2023)
Transforming air traffic from fossil fuels to sustainable air traffic poses new challenges for airports. The charging infrastructure and aircraft fueling at future airports must also adapt to sustainable, electric aviation. This paper presents a MATLAB Simulink model of a future airport using data from a regional airport. This model simulates the initial estimates for an airport's entry into a sustainable aviation industry. Based on a flight plan of the regional airport, the aim is to determine which service levels are required and which options are available for future scenarios. For this purpose, a charging profile for aircraft batteries was created to meet the challenges of short ground times for regional aircraft. The model analyses suitable supply technologies for energy storage on the ground, grid connection and energy transmission to the aircraft.<br

Operating strategies for a Regional Airport to challenge future hybrid-electric aircraft systems - Meindl, Markus; Krödel, Paul-Oliver; Lange, Christopher; März, Martin (AIAA AVIATION Forum, 2024)

Power electronics design for a 50 PAX hybrid-electric regional aircraft - Meindl, Markus; März, Martin; Hilpert, Florian; Bentheimer, Christian (AIAA AVIATION Forum, 2023)
The transition to sustainable aviation plays a crucial role and can be managed by power electronics. The Clean Sky 2 project GENESIS addresses the environmental sustainability of hybrid-electric 50-passenger (PAX) aircraft systems in a life cycle perspective to support the development of a technology roadmap for the transition to sustainable and competitive electric aircraft systems. This article has emerged from the GENESIS research and describes different options for power electronics in a hybrid-electric aircraft. Possible solutions and estimates for the power electronics for 2030, 2040, and 2050 are proposed. This paper presents the required power electronics components for a regional aircraft with a possible range of 1500 km. The power distribution system of the whole aircraft, the HV DC voltage, and the power electronic converters are analyzed. These converters are presented, calculated, designed, and specified. Particular reference is made to the converters' power density and efficiency. The wide band gap materials silicon carbide (SiC) and gallium nitride (GaN) are discussed for the design of the converters.<br

Prospective Life Cycle Inventory Datasets for Conventional and Hybrid-Electric Aircraft Technologies - Thonemann, Nils; Saavedra-Rubio, Karen; Pierrat, Elenore; Dudka, Katarzyna; Bangoura, Mathilde; Baumann, Nils; Bentheimer, Christian; Caliandro, Priscilla; De Breuker, Roeland; De Ruiter, Cor; Di Stasio, Mario; Elleby, Julie; et al. (Social Science Research Network, 2023)
Abstract Hybrid-electric aircraft are often perceived as a potential solution to decarbonize short-haul flights and enhance aviation sustainability. However, making hybrid-electric aircraft a reality should be backed by robust environmental impact analysis because the necessary technology development is investment, time, and research-heavy. In this study, we thus developed a total of 45 prospective life cycle inventories (LCI) for conventional and hybrid electric aircraft configurations and technologies for 2030, 2040, and 2050. The LCI datasets were built following a systematic approach that ensures data harmonization, using scientific literature, industry expert knowledge, and primary data from several industry sources. They cover all relevant systems to model the environmental impacts of flying 200 to 600 nmi with a 50 PAX aircraft from cradle to gate using the ATR42 as a reference aircraft. Additional information for the end-of-life and uncertainty analysis is also provided. The systems in scope include airframe, powertrain, power electronics and drives, batteries, fuel cells, hydrogen onboard storage, airport systems, and battery charging stations. As a test of the datasets, the carbon footprint of the conventional aircraft built from our generated data was consistent with the one obtained using the short-haul aircraft from the ecoinvent v3.8 LCI database. Nonetheless, the disaggregation of the developed LCI datasets is more than ten times more detailed than currently existing ones, and they integrate a prospective dimension. As such, they, therefore, unlock the modeling of the potential environmental impacts of conventional and future aircraft fueled by kerosene or alternative aviation fuels, future hybrid-electric aircraft using batteries, and future hybrid-electric aircraft using hydrogen as fuel in combination with batteries. In that sense, our results contribute to fostering the development of environmentally sounder technology roadmaps for regional aviation.
Keywords: LCA; prospective life cycle assessment; environmental sustainability; data collection; LCI; aviation

Prospective life cycle inventory datasets for conventional and hybrid-electric aircraft technologies - Thonemann, Nils; Saavedra-Rubio, Karen; Pierrat, Eleonore; Dudka, Katarzyna; Bangoura, Mathilde; Baumann, Nils; Bentheimer, Christian; Caliandro, Priscilla; De Breuker, Roeland; de Ruiter, Cor; Di Stasio, Mario; Elleby, Julie; et al. (Journal of Cleaner Production, 2024)
Hybrid-electric aircraft represent a promising solution for the urgent need to decarbonize short-haul flights and bolster aviation sustainability. Nevertheless, the realization of hybrid-electric aircraft demands rigorous environmental impact analysis, given the substantial investments, time, and research required for technology development. This study offers a comprehensive life cycle inventory spanning the years 2030, 2040, and 2050 for both conventional and hybrid-electric aircraft configurations. Our inventory datasets are meticulously constructed through a systematic approach, ensuring data harmonization by drawing upon scientific literature, industry expertise, and primary data sources. This extensive dataset encompasses all pertinent systems necessary to model the environmental footprint of flights covering distances ranging from 200 to 600 nautical miles, utilizing a 50-passenger aircraft with the ATR42 as a reference model. Additionally, we furnish supplemental data for end-of-life considerations and uncertainty analysis. The systems under examination include the airframe, powertrain, power electronics and drives, batteries, fuel cells, hydrogen onboard storage, airport infrastructure, and battery charging stations. Notably, the carbon footprint of conventional aircraft aligns with data from the ecoinvent v3.8 database; however, our provided datasets are more than tenfold more detailed and incorporate a forward-looking perspective. These meticulously curated life cycle inventories can be amalgamated to simulate the potential environmental ramifications of conventional aircraft powered by kerosene or alternative aviation fuels, hybrid-electric aircraft utilizing battery technology, and hybrid-electric aircraft employing hydrogen as a fuel in conjunction with batteries. In this context, our findings play a pivotal role in nurturing the development of technology roadmaps that prioritize environmental sustainability within the realm of regional aviation.
Created from Fastlane, Scopus look-up
Keywords: Aviation; Data collection; Environmental sustainability; Industrial ecology; LCA; Prospective life cycle assessment; Transport

Reverse engineering of the hydrogen system of a commercial fuel cell vehicle - Meindl, Markus; Öchsner, Richard; Geiling, Johannes; März, Martin (2023 IEEE 32nd International Symposium on Industrial Electronics (ISIE), 2023)
This paper comprises a complete reverse engineering of a Toyota Mirai. The hydrogen system of this commercial fuel cell vehicle (FCV) was comprehensively analysed. The level of consideration includes all non-destructively accessible aspects such as mechanical design principles, functional analyses, and material and component selection up to the interfaces to the vehicle. The most important operating data, functions and error messages for a laboratory's recommissioning system were extracted. All relevant operating parameters were read out live on a test track and could then be interpreted and described. In the next step, the complete hydrogen system, including batteries, power electronics and wiring harness, was removed from the vehicle. Considering the safety requirements, the vehicle's components were reassembled in a hydrogen laboratory. With the integration of the necessary signals, the error messages were successfully eliminated to put the system back into operation in the laboratory gradually. Particular importance has been attached to the comprehensive documentation of the findings. The individual components are described and explained in great detail. Finally, possibilities for the continuation of the project are presented as a suggestion.<br
Keywords: hydrogen; fuel cell vehicle; reverse engineering; automotive applications